Asymmetric collaboration in virtual reality: A taxonomy of asymmetric interfaces for collaborative immersive learning - Albæk Thomsen, Lui; Nilsson, Niels Christian; Nordahl, Rolf; Lohmann, Boris (Tidsskriftet Læring og Medier (LOM), 2019)
It has been established that Virtual Reality (VR) possesses certain qualities for educational purposes. These include the ability to place the learner at the location or in the perspective that the desired knowledge exists (e.g., travelling to another planet or shrinking to miniature size to observe internal anatomy). VR is also considered to contribute with enriching the curricular content, promoting active forms of learning, performance assessment of high validity, and provide the opportunity to teach applied academic knowledge in life-like situations. In regards to teaching mathematics and geometry, three key affordances have been identified; interactive manipulation and construction of three-dimensional geometry, comprehension of spatial relationships, and rectification of abstract problems. Safety protocols and practical guidelines from classroom experimentation have also been formulated by various research projects. In this manuscript, asymmetrical immersive VR in education will be reviewed, as it is relevant for the narrative of learning situations where multiple students use the technology together. As an example, in mathematics, asymmetric VR could be used in contexts where unknown variables must be found in collaboration. The purpose of the narrative literature review is to gain a greater understanding of how asymmetric game mechanics has influence on communication and collaboration between learners. To map the dynamics of this type of learning activity, a taxonomy will be presented. Since VR is still under development in terms of hardware and software, it is important that the current and future technical possibilities are described in a conceptual manner, as well as conclude on optimal coupling between communication dynamics and collaboration mechanics.